Estimating the economic impact of tourism in German wine regions - Maximilian Tafel; Gergely Szolnoki (International Journal of Tourism Research, 2020)
With an economic impact of EUR 291 billion, Germany is the number-one European country in terms of tourism revenue. German wine regions have a long history of production, but the value of these regions as tourism destinations has only recently received recognition. In the last few years, wine tourism has gained increasing importance and is believed to result in sustainable development by creating jobs while at the same time preserving a region's heritage. The aim of this paper is to estimate the economic impact of tourism in German wine regions in order to help stakeholders make the right policy and investment decisions. Therefore, a modified multiplier model was developed that allows for the economic impact of wine tourism to be assessed. By collecting 4,448 questionnaires in all 13 German wine regions, travelers provided information about their travel behavior, expenditures, and socio-demographic characteristics. After conducting segmentation, the economic impact of tourism as well as wine tourism was estimated for each of the wine regions. The results show that tourism in German wine regions has an economic impact of EUR 26.4 billion, providing 384,878 people with their primary income. Due to higher expenditures, wine tourists show a disproportionately high economic impact of EUR 5.0 billion, which makes this niche market generate income for 71,846 people. The right investments in this lucrative market could help balance regional economic disparities and achieve sustainable tourism development in the country.
Keywords: 300; economic impact; Germany; multiplier model; tourism; wine; wine tourism